ANALISIS PEMILIHAN SUPPLIER SPAREPARTSTRANFORMATOR DENGAN METODE FUZZY ANALYTICAL HIERARCHY PROSES(F-AHP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEALSOLUTION (TOPSIS) PADA PT. XYZ - Clarissa Vadya Azarine (2022)
PT. XYZ is one of the largest paper providers in Indonesia. The problems faced by the company PT. XYZ is when purchasing transformer spare parts, companies should choose suppliers carefully because problems frequent delivery delays, Delivery of the wrong number of products, and defects during delivery, so they need the best supplier to solve these problems. In this study, researchers used the Fuzzy AHP and TOPSIS methods. AHP is used to solve complex problems into a hierarchical form, and fuzzy logic is used to reduce the uncertainty value in AHP. In this study, 3 criteria and 14 criteria were used, which after being cut off became 10 sub-criteria. If it is calculated using the Fuzzy AHP method, the main criterion chosen is the price criterion with a weight value of 0.730. The results of this study show that from five suppliers, namely TI, SS, BD, QI and FE. the best alternative chosen to use the TOPSIS method is the BD supplier with the highest preference value of 0.394.